Kesulitan Membaca pada Siswa Kelas 3 SDN 3 Tanjung: Analisis dan Faktor Penyebab - Maharani, Ananda; Ibrahim, Ibrahim; Witono, Hari; Suranti, Ni Made Yeni (Indonesian Publication Center, 2024)
Grade 3 elementary school (SD) students still experience significant reading difficulties. The results of this research show that the majority of students in class 3 at SDN 3 Tanjung have difficulty reading, especially in the lower classes. Reading difficulties can affect students' self-confidence and learning achievement. Students' initial abilities, learning approaches, and students' internal factors are several factors that influence reading difficulties. Therefore, there needs to be action taken to improve the reading ability of students in class 3 of SDN 3 Tanjung including the use of effective learning strategies and individual guidance.